2017
DOI: 10.1017/s175173111600152x
|View full text |Cite
|
Sign up to set email alerts
|

Early neonatal lamb mortality: postmortem findings

Abstract: An investigation of stillbirth and early neonatal lamb mortality was conducted in sheep flocks in Norway. Knowledge of actual causes of death are important to aid the interpretation of results obtained during studies assessing the risk factors for lamb mortality, and when tailoring preventive measures at the flock, ewe and individual lamb level. This paper reports on the postmortem findings in 270 liveborn lambs that died during the first 5 days after birth. The lambs were from 17 flocks in six counties. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In sheep, two papers noted that stillbirth and perinatal mortality rates were higher than at any age ( Holmoy & Waage, 2015 ); Voigt et al , 2019 ), while other authors report the largest proportion of mortalities occurred within 24 hours of birth ( Binns et al ., 2002 ), or within first week ( Gokce & Erdogan, 2009 ; Gokce et al ., 2013 ; Khan et al ., 2006 ). Holmoy et al . (2017) reported that 80% of neonatal lamb mortalities occurred within the first two days of life.…”
Section: Resultsmentioning
confidence: 99%
“…In sheep, two papers noted that stillbirth and perinatal mortality rates were higher than at any age ( Holmoy & Waage, 2015 ); Voigt et al , 2019 ), while other authors report the largest proportion of mortalities occurred within 24 hours of birth ( Binns et al ., 2002 ), or within first week ( Gokce & Erdogan, 2009 ; Gokce et al ., 2013 ; Khan et al ., 2006 ). Holmoy et al . (2017) reported that 80% of neonatal lamb mortalities occurred within the first two days of life.…”
Section: Resultsmentioning
confidence: 99%
“…Holmoy et al 42 suggested that the relative frequency of certain diagnosed causes of perinatal death (eg, dystocia or hypogammaglobulinaemia) in flocks which lamb indoors may differ from those which lamb outdoors due to differences in the intensity of lambing surveillance. Data on whether sheep were due to lamb indoors or outdoors were unavailable in this study and it is possible, therefore, that the overall number of submissions, and those of perinates specifically, may have been influenced by the lambing system on farm.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of petechial hemorrhages on different organs such as the heart and spleen indicated septicemia. Holmoy et al [18] recorded that E. coli existed among 65% of the septicemic lambs. Ruminants, particularly sheep and cattle, are recognized as reservoirs of E. coli (STEC) strains [19].…”
Section: Discussionmentioning
confidence: 99%